1989
DOI: 10.1104/pp.89.1.341
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Composition of Maize Kernels Cultured in Vitro with Varying Supplies of Carbon and Nitrogen

Abstract: This study employed in vitro seed culture to determine how C and N supply influence the growth (i.e. starch accumulation) and protein composition of maize (Zea mays L.) endosperm. Immature kemels were grown to maturity on liquid medium containing various concentrations of C (sucrose at 234 millimolar [low] and 468 millimolar [high]) and N (amino acid mixture ranging in N from 0 to 144 millimolar). Low C supply limited starch, but not N, accumulation in the endosperm. With high C, endosperm starch and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…Dry matter and storage proteins are accumulated, suggesting that in the endosperm cells the nOmxil developmental processes continue after isolation from the plant, if sucrose and a source of N are supplied. The finding is in good agreement with previous observations indicating that in vitro cultures of maize kernels and endosperm cells allow the study of grain growth and protein synthesis during development (Balconi eta/., 1991 ;Lyznick and Tsai, 1989;Manzocchi, 1991 ;Singletary and Below. 1989;Singletary etal., 1990).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Dry matter and storage proteins are accumulated, suggesting that in the endosperm cells the nOmxil developmental processes continue after isolation from the plant, if sucrose and a source of N are supplied. The finding is in good agreement with previous observations indicating that in vitro cultures of maize kernels and endosperm cells allow the study of grain growth and protein synthesis during development (Balconi eta/., 1991 ;Lyznick and Tsai, 1989;Manzocchi, 1991 ;Singletary and Below. 1989;Singletary etal., 1990).…”
Section: Discussionsupporting
confidence: 82%
“…Available evidence indicates that the coordinate expression of zein gene classes occurs rnostty at the levd of transcription (reviewed in Motto eta/., 1989). In addition, recent data (Lyznick and Tsai, 1989;Singletary and Below, 1989 The results reported here indicate that wild-type and 02 endosperms of 9 DAP continue to develop for at least 5 days when cultured on simple defined media. Dry matter and storage proteins are accumulated, suggesting that in the endosperm cells the nOmxil developmental processes continue after isolation from the plant, if sucrose and a source of N are supplied.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Exemplifying this relationship, it has been demonstrated numerous times that kernel weights increase when crops of maize are supplemented with increasing levels of N fertilizer (3,7). Recently, with the aid of in vitro techniques, it was demonstrated that starch and N accumulation in the endosperm of maize kernels increased as the concentration of N available to the kernel increased (23). Similar studies have shown corresponding responses for wheat (4) and barley (14).…”
mentioning
confidence: 51%
“…From a similar standpoint, it is well known that the accumulation of zeins, the primary storage proteins of maize kernels, responds dynamically to N nutrition (23,26). Because the amino acid composition of the zein fraction does not change significantly as a function of N accumulation in the kernel, it would seem that different zeins are always produced in equally proportional amounts (16).…”
mentioning
confidence: 99%